Biomedical Enhancement and Social Development: A Conservative Techno‐Fix. (26th September 2016) - Sanyal, Sagar
Abstract: Allen Buchanan has argued for a linking of the ethics of human enhancement to the ethics of development more generally. The promise of the 'enhancement enterprise' is that it may help develop society, just as other technological advances have in the past. He proposes a framework of intellectual property rights, government action to ensure the poor can access the enhancements, an international organization to administer the diffusion of new enhancement technologies from the West to poor countries, and the diffusion within countries to the poorer populations. I take seriously his proposal of discussing biomedical enhancement in terms of the ethics of development. On these grounds of assessment, I argue that his proposal is politically conservative. To make the case, I distinguish conservatism in ethics from conservatism in politics; and I contextualize the proposal against the background of development economics and the neoliberal approach to development.